The Effect of Good Corporate Governance, Company Growth, Company Size and Earnings Management on Capital Structure - Mulyadi, Olandari; Dodi suryadi; Berta Agus Petra; Suchi Avita Rici (Economics and Digital Business Review, 2024)
This article analyzes the influence of good corporate governance, company growth, company size and earnings management on capital structure. This research on manufacturing companies was selected using a purposive sampling method. The analysis was carried out using SPSS 25. The results showed that Capital Structure (Y) had a minimum value of 0.10, a maximum value of 2.72, a mean value of 1.6248 and a standard deviation of 0.62031. then Ho is rejected and H1 is accepted. Thus, the first hypothesis is accepted. Company Growth (X2) has a minimum value of 0.20, a maximum value of 2.63, a mean value of 1.3361 and a standard deviation of 0.29018. So the second hypothesis is accepted. Company size (X3) has a minimum value of 5.08, a maximum value of 5.79, a mean value of 5.3792 and a standard deviation of 1.5288. So the third hypothesis is accepted. Earnings Management (X4) has a minimum value of 0.80, a maximum value of 4.12, a mean value of 2.4875 and a standard deviation of 0.62838. So the fourth hypothesis is accepted.